Characterization of almond kernel oils of five almonds varieties cultivated in Eastern Morocco - Houmy N.; Mansouri F.; Benmoumen A.; Elmouden S.; Boujnah M.; Sindic M.; Fauconnier M-L.; Serghini-Caid H.; Elamrani A. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
This study focuses on characterization of almond kernel oils extracted mechanically from five sweet almond varieties: ‘Marcona’, ‘Fournat’, ‘Ferragnes’, ‘Ferraduel’ and ‘Beldi’), cultivated in eastern Morocco. Oil content, physicochemical parameters, triacylglycerol and fatty acid compositions were determined. Analyzed oils showed low acidity values that range between 0.77-0.88%, peroxide values range between 6.43-16.39 meq/kg and Iodine values range between 98.42-103.90%. The principal fatty acid of almond kernel oils is oleic acid (C18:1); oils of ‘Ferragnes-Ferraduel’ and ‘Beldi’ varieties show higher values of C18:1 respectively of 72.87 and 71.62%, however ‘Fournat’ almond kernel oil shows the lowest content of C18:1 (63.54%). HPLC analysis of triglycerides was carried out, and results show that analyzed almond kernel oils are characterized by the dominance of trioleylglycerol (OOO) that contents range between a minimum of 31.48% for Fournat’s oil and 43.82% for Ferragnes-Ferraduel’s oil. The oxidative stability of almond kernel oils was determined by rancimat tests as the induction period (IP, h recorded by a 743 Rancimat apparatus Metrohm, Switzerland). Results show that stability, of almond kernel oils is clearly influenced by the almond variety; Oxidative stability of tested almond kernel oils ranged between an IP = 20.28 h for ‘Marcona’ oil and an IP = 27.55 h for ‘Ferragnes-Ferraduel’.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)